2006
DOI: 10.1007/s10661-006-9549-2
|View full text |Cite
|
Sign up to set email alerts
|

Residual fate and persistence of endosulfan (50 WDG) in Bengal gram (Cicer arietinum)

Abstract: Residual fate and dissipation pattern of endosulfan (50 WDG) in soil and plant was studied by gas liquid chromatography following twice applications (at 350 g and 700 g a.i. ha(-1)) in chick-pea, Bengal gram (Cicer arietinum) at vegetative and flowering stages of the crop. The initial residues of Endosulfan (alpha + beta + endosulfan sulfate) in plant following second application was 23.40-57.91 microg g(-1) and its maximum deposit in soil was 1.00-2.45 microg g(-1) after 1 day. Dissipation followed first orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The presence of β-endosulfan seems to be a useful indicator of time since exposure to endosulfan (Nowak et al, 1995). The overall average of α/β endosulfan in this study was 0.9, indicating ongoing use of technical endosulfan (Chakraborty et al, 2010;Chowdhury et al, 2007;Kole et al, 2001).…”
Section: Endosulfanmentioning
confidence: 56%
See 1 more Smart Citation
“…The presence of β-endosulfan seems to be a useful indicator of time since exposure to endosulfan (Nowak et al, 1995). The overall average of α/β endosulfan in this study was 0.9, indicating ongoing use of technical endosulfan (Chakraborty et al, 2010;Chowdhury et al, 2007;Kole et al, 2001).…”
Section: Endosulfanmentioning
confidence: 56%
“…In India, organochlorine pesticides have been reported in various matrices including food commodities (Aktar et al, 2009;Chakraborty et al, 2010;Chowdhury et al, 2007;Devanathan et al, 2009;Guzzella et al, 2005;Kole et al, 2001;B. Kumar et al, 2009;Senthilkumar et al, 2001;Someya et al, 2009;Zhang et al, 2008).…”
mentioning
confidence: 99%
“…The concentrations of these pollutants observed in many agricultural soil samples were very high (Al-Wabel et al, 2011;Hoai et al, 2010;Kumari et al, 2008;Liu et al, 2009;Senthilkumar et al, 2009;Xu et al, 2013a,b). A number of studies revealed the prevalence of OCPs and PCBs in various environmental matrices, including food commodities in India (Aktar et al, 2009;Chakraborty et al, 2010;Chowdhury et al, 2007;Devanathan et al, 2009;Guzzella et al, 2005;IPEN, 2006;Kole et al, 2001;Kumar et al, 2009;Prakash et al, 2004;Senthilkumar et al, 2001;Someya et al, 2009;Zhang et al, 2008). Today, everything from food to groundwater and drinking water is contaminated severely with OCPs, therefore understanding the environmental fate of OCP residues is a key issue.…”
Section: Introductionmentioning
confidence: 99%
“…Since endosulfan and its breakdown products are persistent in the environment with an estimated half-life of 0.7-6 years [2]. Contamination and persistence of endosulfan in aquatic and soil environments lead to accumulation in crop, tea, phytoplankton, zooplankton, fishes and vegetables [3][4][5][6]. It is extremely toxic to fish and aquatic invertebrates and affects the central nervous system, kidney, liver, blood chemistry and parathyroid gland, which has reproductive, teratogenic, and mutagenic effects [7][8][9].…”
Section: Introductionmentioning
confidence: 99%